The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/agronomy10091401
|View full text |Cite
|
Sign up to set email alerts
|

Association between Productivity, Fatty Acid Profiles, Oil Bodies’ Ultrastructure and Molecular Markers in Peanut (Arachis hypogaea L.) Cultivars

Abstract: The commercial Nigerian peanut cultivars Ex-Dakar, Samnut-22 and Samnut-26, the Egyptian cultivar Ismailia-1 and the American cultivar NC-7 were genetically differentiated and the cultivars’ effects on growth and yield components, total lipid contents, including saturated and unsaturated fatty acids, and oil body size and number were investigated. Experiments were carried out at Cairo University Research Station, Giza, Egypt, during the summer seasons of 2016 and 2017. All cultivars had high contents of total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…It has been found that peanut varieties with high oleic acid could maintain better taste quality and long‐term stability of seed quality during storage (Liu, Chen, et al, 2019; Martín et al, 2018; Wen et al, 2018). And the oleic acid content gradually increased while linoleic acid showed a downward trend (Abbas et al, 2020; Bishi et al, 2013). Similar rules were also obtained in this study.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that peanut varieties with high oleic acid could maintain better taste quality and long‐term stability of seed quality during storage (Liu, Chen, et al, 2019; Martín et al, 2018; Wen et al, 2018). And the oleic acid content gradually increased while linoleic acid showed a downward trend (Abbas et al, 2020; Bishi et al, 2013). Similar rules were also obtained in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Peanut or groundnut (Arachis hypogaea L.) is one of the important oil crops of the kharif season. It is widely grown in tropical and subtropical regions of the world [1]. It belongs to the genus Arachis and the family Leguminosae.…”
Section: Introductionmentioning
confidence: 99%
“…"Peanut or groundnut (Arachis hypogaea L.) is one of the important oil crops of the kharif season. It is widely grown in tropical and subtropical regions of the world" [1]. "It belongs to the genus Arachis and the family Fabaceae.…”
Section: Introductionmentioning
confidence: 99%